Long‐term microbial community dynamics at two full‐scale biotrickling filters treating pig house exhaust air. Issue 4 (20th May 2019) - Van der Heyden, Caroline; De Mulder, Thijs; Volcke, Eveline I. P.; Demeyer, Peter; Heyndrickx, Marc; Rasschaert, Geertui
Summary: In this study, the microbial community structure of two full‐scale biotrickling filters treating exhaust air from a pig housing facility were evaluated using 16S metabarcoding. The effect of inoculation with activated sludge of a nearby domestic waste water treatment plant was investigated, which is a cheap procedure and easy to apply in practice. The study was performed at a three‐stage and a two‐stage full‐scale biotrickling filter; of which, only the latter was inoculated. Both biotrickling filters evolved towards a rather similar community over time, which differed from the one in the activated sludge used for inoculation. However, the bacterial population at both biotrickling filters showed small differences on the family level. A large population of heterotrophic bacteria, including denitrifying bacteria, was present in both biotrickling filters. In the non‐inoculated biotrickling filter, nitrite‐oxidizing bacteria (NOB) could not be detected, which corresponded with the incomplete nitrification leading to high nitrite accumulation observed in this system. Inoculation with the wide spectrum inoculum activated sludge had in this study a positive effect on the biotrickling filter performance (higher ammonia removal and lower nitrous oxide production). It could thus be beneficial to inoculate biotrickling filters in order to enrich NOB at the start‐up, making it easier to keep the free nitrous acid concentration low enough to not be inhibited by it. Abstract : This contribution concerns a research paper about the microbial community structure of two biotrickling filters installed at pig housing facilities. These systems are frequently installed at pig housing facilities to remove ammonia from the outgoing air and to nitrify the absorbed ammonia/ammonium to nitrate. 16S metabarcoding was performed to follow up fluctuations and variations in time but also in space. Additionally, the effect of inoculation of one of the two systems with activated sludge of a wastewater treatment plant was investigated.